Social isolation and hospitalizations of older adults due to falls in an emergency hospital: a cross-sectional study (Revista Contexto & Saúde, 2026)
Objective: The aim of this study was to describe the profile of older adults hospitalized due to falls and to compare the prevalence of accidents during the period from January 2019 to December 2020. Method: This retrospective observational study was conducted through data collection from electronic medical records at the Emergency Hospital of Porto Alegre, Rio Grande do Sul, Brazil. Results: A total of 514 hospitalizations due to falls were recorded, 71.4% of which occurred in women. Of these cases, 75.3% were same-level falls, and 92% occurred within the patients’ own homes. Among them, 93.3% were associated with fractures, with proximal femur fractures being the most prevalent (57.6%). The months with the highest prevalence of falls in 2019 were May, June, July, and September, showing a significant difference compared to the other months (p = 0.004). In contrast, during the pandemic year of 2020, the distribution of falls was homogeneous throughout the year (p = 0.249). Conclusion: The present study showed a relatively homogeneous distribution of falls during the COVID-19 pandemic; however, the frequency increased compared to previous years. It is likely that restrictions related to cold weather, home confinement, and reduced sun exposure influenced the occurrence of falls.